Ontological dependence in a spacetime-world - Tallant, Jonathan (Springer, 2015)
Priority Monism (hereafter, ‘Monism’), as defined by Jonathan Schaffer (Philos Rev 119:131–176, 2010), has a number of components. It is the view that: the cosmos exists; the cosmos is a maximal actual concrete object, of which all actual concrete objects are parts; the cosmos is basic—there is no object upon which the cosmos depends, ontologically; ontological dependence is a primitive and unanalysable relation. In a recent attack, Lowe (Spinoza on monism. Palgave Macmillan, London, pp 92–122, 2012) has offered a series of arguments to show that Monism fails. He offers up four tranches of argument, with different focuses. These focal points are: (1) being a concrete object; (2) aggregation and dependence; (3) analyses of ontological dependence; (4) Schaffer’s no-overlap principle. These are all technical notions, but each figures at the heart of a cluster of arguments that Lowe puts forward. To respond, I work through each tranche of argument in turn. Before that, in the first section, I offer a cursory statement of Monism, as Schaffer presents it in his 2010 paper, Monism: The Priority of the Whole. I then respond to each of Lowe’s criticisms in turn, deploying material from Schaffer’s 2009 paper Spacetime: the One Substance, as well as various pieces of conceptual machinery from Lowe’s own works (The possibility of metaphysics. Clarendon, Oxford, 1998, 2010) to deflect Lowe’s (Spinoza on monism. Palgave Macmillan, London, pp 92–122, 2012) attacks. In the process of defending Monism from Lowe (Spinoza on monism. Palgave Macmillan, London, pp 92–122, 2012), I end up offering some subtle refinements to Schaffer’s (Philos Rev 119:131–176, 2010) view and explain how the resulting ‘hybrid’ view fares in the wider dialectic.